PERLINDUNGAN HUKUM BAGI PEMEGANG SAHAM TERKAIT SENGKETA PENGUASAAN TANAH OLEH PERUSAHAAN - Wati, Rika Sandra Vika; Felicitas Sri Marniati; Taqiyuddin Kadir (Journal of Innovation Research and Knowledge, 2025)
The issue addressed in this study focuses on the control of land by a company and its implications for the protection of shareholders’ rights, as reflected in Decision No. 154/Pdt.G/2023/PN Smg, Decision No. 100/Pdt.G/2024/PN Lbp, and Decision No. 123/Pdt.G/2021/PN Smg. The research problems formulated in this study are: (1) How is the dispute between shareholders and the company regarding the control of shareholders’ land resolved? and (2) How is legal protection provided for shareholders in relation to land control by the company? The theories employed in this study are the Theory of Legal Protection by Satjipto Rahardjo and the Theory of Dispute Resolution by Dean G. Pruitt and Jeffrey Z. Rubin. This research adopts a normative juridical approach, which is a legal study based on literature or secondary data, utilizing primary, secondary, and tertiary legal materials. The research employs several approaches, namely the statutory approach, case approach, analytical approach, and conceptual approach. Legal materials were collected through the identification and inventory of positive legal rules, literature, books, journals, and other legal sources. The analysis of legal materials was conducted using legal interpretation—specifically grammatical and systematic interpretation—and legal construction methods, including analogy construction and the refinement of law (rechtsverfijning). The findings reveal that legal protection for shareholders in the context of corporate land control continues to face obstacles, both in terms of regulation and implementation. Although, in normative terms, company law clearly separates corporate assets from the personal property of shareholders, practical realities indicate that abuse of authority by management or majority shareholders still occurs frequently